Tooth Loss Is Associated With Increased Risk of Dementia and With a Dose-Response Relationship - Chen, Jun; Ren, Chang-Ju; Wu, Lan; Xia, Ling-Yun; Shao, Jun; Leng, Wei-Dong; Zeng, Xian-Tao (Frontiers in Aging Neuroscience, 2018)
Objective: Both tooth loss and dementia are age-related frequently-occurring diseases, and increasing attentions have been paid to explore the pathogenesis related to oral-brain function disorders. The present study was performed to evaluate the association between tooth loss and dementia through a dose-response meta-analysis. Methods: Relevant cohort studies were searched from online databases up to June 20, 2018, which examined the association between tooth loss and the risk of dementia. Literature selection according to inclusion and exclusion criteria, and data extraction from included studies were completed independently by two reviewers. Data syntheses in this meta-analysis were performed using Stata 12.0 software. Results: A total of 8 cohort studies were included, containing a total of 14362 cases and 2072 dementia patients. The result of the meta-analysis indicated that patients with tooth loss faced 1.34 times greater risk of developing dementia (RR = 1.34，95% CI = 1.19-1.51). Meanwhile, the result from this dose-response meta-analysis in a linear model suggested that every missed tooth might increase the risk of dementia by 1.01 times (RR= 1.01, 95%CI = 1.00-1.02). Further subgroup analyses pointed out that tooth loss patients without dentures may have higher risk of dementia than those with dentures (with denture: RR = 0.98, 95% CI = 0.87-1.10; without denture: RR = 1.53, 95% CI = 1.19-1.97), meanwhile, study design, study area and education level of study participants might also have some effect on the results. Conclusions: Tooth loss may be a risk factor for the development of dementia. Besides, there is a dose-response relationship along with the missed tooth increased.